1999
DOI: 10.1021/es990738k
|View full text |Cite
|
Sign up to set email alerts
|

Historical Trends of N-Cyclohexyl-2-benzothiazolamine, 2-(4-Morpholinyl)benzothiazole, and Other Anthropogenic Contaminants in the Urban Reservoir Sediment Core

Abstract: A new potential molecular marker, N-cyclohexyl-2benzothiazolamine (NCBA), was discovered in various environmental matrices (i.e., road dusts, runoff-and riverwater particles, river sediments, aerosols) taken in Tokyo, Japan. Concurrent determination of this compound together with 2-(4-morpholinyl)benzothiazole (24MoBT), previously proposed marker of road dust, demonstrated that both compounds are widely distributed in the urban environment (∼ng/g to ∼µg/g), derived from vehicle tire tread, and transported in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
66
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 31 publications
(35 reference statements)
8
66
2
Order By: Relevance
“…The impact of automobile emissions on environment, predominantly on soil, air and water is increasing day by day. Automobile emissions have shown a tremendous impact on the environment during the past few years (Kumata et al, 2000). One of the toxic contaminants found in roadside soil and dust includes PAHs.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of automobile emissions on environment, predominantly on soil, air and water is increasing day by day. Automobile emissions have shown a tremendous impact on the environment during the past few years (Kumata et al, 2000). One of the toxic contaminants found in roadside soil and dust includes PAHs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the initially applied parent compounds such as TCMTB or MoTBT were not detected, as these undergo quick transformation (6,10). Instead, putative transformation products such as BT and MTBT (5,7,(11)(12)(13) or stable byproducts such as 2-(4-morpholinyl)-benzothiazole or N-cyclohexyl-2-benzothiazole (14) were detected. These detections were often only qualitative or semiquantitative and most studies on the occurrence of benzothiazoles in wastewater or surface water were limited to isolated samples.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the origin of PAHs in road dust were mainly from automobile exhaust [14,20], road pavement material or asphalt [14,21], tire rubber, and lubricant oil [21]. Similar to aerosols, road dust will be deposited onto the surface water by rain [22,23] bringing along the PAHs into the water reservoirs. The concentrations of PAHs in road dust vary with the distance of its sources [24].…”
Section: Introductionmentioning
confidence: 99%